Glove Perforation in Orthopaedic Surgery: Pattern and Predictors - Ajibade, Adesina; Oluwadiya, Kehinde Sunday; Olaitan, Peter Babatunde; Ogunlusi, Johnson Dare (Nigerian Journal of Orthopaedics and Trauma, 2020)
Background: Intact surgical gloves prevent transmission of pathogens between the surgeon and the patient. However, gloves may be breached during surgical operations with risk of cross‑transmission of pathogens between the surgeon and the patient. This study aimed to determine the incidence, nature and predictors of glove perforations in orthopaedic surgery. Methods: Gloves worn by the surgeon, their assistants and the scrub nurse were tested. Number, position and nature of perforations were recorded and analysed. Binary logistic regression was used to assess the impact of six possible predictors on the likelihood of glove perforation. Results: The operative glove perforation rate was 72.2%. Perforations occurred more on the nondominant hand (62.4%) and on outer gloves (85.8%). They were more common among surgeons and their assistants than scrub nurses and in trauma and implant operations than other surgeries. Only 27.1% of glove perforations were detected intraoperatively. The status of operative personnel and duration of surgery were predictive of glove perforation. Conclusions: Glove perforation is common in orthopaedic operations and was predicted by status of the surgeon and the duration of surgery. Double gloving provides a better barrier to contamination of surgeon’s skin by patients’ body fluids than single gloving; however, sometimes, the barrier can still fail. We recommend that double‑gloving be routinely used in orthopaedic surgery, especially where complex instrumentations are employed.